Computation of non-Newtonian quadratic convection in electro-magneto-hydrodynamic (EMHD) duct flow with temperature-dependent viscosity - Zhang, Lijun; Bhatti, Muhammad Mubashir; Beg, Osman Anwar; Ellahi, Rahmat; Öztop, Hakan Fehmi (Sage Publications Ltd, 2023)
Motivated by novel developments in smart non-Newtonian thermal duct systems, a theoretical study has been presented in this article for electro-magneto-hydrodynamic (EMHD) buoyancy-driven flow of a fourth-grade viscoelastic fluid in a vertical duct with quadratic convection. The viscosity of the fourth-grade fluid model is assumed to be temperature-dependent, and the Reynolds exponential model is deployed. Viscous heating and Joule dissipation effects are included. The duct comprises a pair of parallel electrically insulated vertical flat plates located a finite distance apart. Via suitable scaling transformations, a nonlinear boundary value problem is derived for the momentum and heat transport. A homotopy perturbation method (HPM) solution is obtained coded in Mathematica symbolic software. There is a considerable enhancement in wall skin friction with an increment in fourth-grade fluid parameter, Brinkman number, electrical field parameter, thermal buoyancy parameter, and quadratic thermal convection parameter. However, skin friction is strongly reduced with a rise in variable viscosity parameter, Hartmann (magnetic) number, and electromagnetic heat generation to conduction ratio. Nusselt number magnitudes are elevated with increase in variable viscosity parameter, thermal buoyancy parameter, and quadratic thermal convection parameter, whereas they are significantly suppressed with increment in fourth-grade fluid parameter, Brinkman number, and Hartmann magnetic number.
Keywords: Fourth-grade viscoelastic fluid; EMHD; quadratic convection; temperature-dependent viscosity; viscous and Joule heating; homotopy perturbation solution